Angiodysplasia in von Willebrand Disease: Understanding the Clinical and Basic Science - Selvam, Soundarya; James, Paula (Seminars in Thrombosis and Hemostasis, 2017)
Severe and intractable gastrointestinal bleeding caused by angiodysplasia is a debilitating problem for up to 20% of patients with von Willebrand disease (VWD). Currently, the lack of an optimal treatment for this recurrent problem presents an ongoing challenge for many physicians in their management of affected patients. Over the past few years, studies have pointed to a regulatory role for the hemostatic protein, von Willebrand factor (VWF), in angiogenesis, providing a novel target for the modulation of vessel development. This article will review the clinical implications and molecular pathology of angiodysplasia in VWD.
Keywords: angiodysplasia; gastrointestinal bleeding; Heyde's syndrome; von Willebrand disease; von Willebrand factor